PENGARUH PENGGUNAAN PORNOGRAFI TERHADAP GEJALA DEPRESI DIMODERASI ORIENTASI RELIGIUS PADA SISWA SMA DI JAWA BARAT - Jihad Javier Jaafar, - (2023)
This research was conducted with the object of examining the impact of pornography use on depressive symptoms moderated by religious orientation. The subject of this research are 400 moslem high school students in province of West Java. This research is performed using the quantitative method. Sampling in this study is conducted using purposive sampling. The data analysis technique used is Simple Linear Regression. To find out the role of religious orientation as a moderator, a Categoric Moderation Test is conducted. The result of this study finds that pornography use does not influence depressive symptoms, however it is discovered that there are differences in the levels of pornography use and religious orientation among different ethnic groups, and across several other demographics. It is recommended that further research is conducted using different methods that would allow the respondents to be more open about their pornography use. Key Words: Pornography use, religious orientation, depressive symptoms, depression.